Application of Laparoscopic Technique in the Treatment of Hepatolithiasis. Issue 2 (April 2021) - Yao, Dianbo; Wu, Shuodong
Abstract : Hepatolithiasis is commonly encountered in Southeastern and East Asian countries, and its incidence is increasing in Western countries. For symptomatic hepatolithiasis or asymptomatic hepatolithiasis with signs of liver atrophy or malignancy, surgical intervention is needed, especially when peroral cholangioscopy and percutaneous transhepatic cholangioscopic lithotomy are not suitable or fail to be performed. Currently, laparoscopic surgery is gradually replacing traditional open surgery and becoming a better option. Various types of laparoscopic surgeries, including laparoscopic hepatectomy, laparoscopic biliary exploration through the common bile duct or the hepatic duct stump, and robotic-assisted laparoscopic surgery, have been developed for the treatment of simple hepatolithiasis, hepatolithiasis concomitant with choledocholithiasis, recurrent hepatolithiasis, and complicated hepatolithiasis. The related clinical experience is gradually accumulating. In this review, the laparoscopic applications and their advantages will be summarized. In most cases, the laparoscopic technique could provide the advantages of less trauma, reduced blood loss, and faster postoperative recovery.